IDENTIFICATION OF GEOCHEMICAL MARKERS OF VOLCANISM BY THE CLUSTER ANALYSIS FOR THE BOTTOM SEDIMENTS OF THE THERMAL LAKE FUMAROLNОЕ ACCORDING TO SR-XRF - I. S. Kirichenko; E. V. Lazareva; S. M. Zhmodik (Геодинамика и тектонофизика, 2022)
We carried out layer-by-layer scanning (with a step of 1 mm) of the bottom sediments of the thermal lake Fumarolnое with SR-XRF (X-ray fluorescence analysis using synchrotron radiation). The lake is located in the caldera of the Uzon volcano (Kamchatka). The section of the bottom sediments of lake IV Fumarolnое covering the time interval from 260 AD to 2012 is diverse in chemical and mineral composition. Two pyroclastic horizons are observed. The chemical composition of the bottom sediments showed the presence of different layers in which such chemical elements as: Ca, Sr, As, Sb, Mo. Cluster analysis performed for chemical elements revealed the boundaries of layers with different geochemical characteristics. The boundaries of these layers coincide with the horizons identified by mineralogical analysis. At the same time, statistical methods of geochemical data processing allowed unambiguously identifying pyroclastic horizons by elemental composition. We show that the data of SR-XRF analysis in conjunction with cluster analysis can be used to separate the gravity core into layers. The data are in good agreement with the separation data into layers using mineralogical methods.